Penjatah Pupuk Granular Laju Variabel Untuk Tanaman Jagung - Muhammad Tahir Sapsal; Samsuar Samsuar (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2020)
The need for corn has increased along with population growth. The increase in needs must of course be accompanied by an increase in corn production, one of which is by meeting the needs of plant nutrients during growth. In order to optimize plant growth, precision fertilization Need to be apply. However, the unavailability of precision fertilizer applicator for corn plants is an obstacle. This research is expected to be able to provide a precision rationing unit design for granular fertilizer in corn cultivation. The rationing unit is built using a 24 V 200 rpm DC motor and is controlled using an Arduino mega module. Allotment uses a rotor with a volume of 26.52 cm3 / rotation. Control using PID. The fertilizer used is NPK fertilizer. The test results show that the system can control fertilizer rationing with a 96% determination coefficient. And able to aplly NPK fertilizer up to 2 tons / ha.